The triple benefits of slimming and greening the Chinese food system - Wang, Xiaoxi; Bordirsky, Benjamin Leon; Müller, Chrisoph; Chen, Kevin Z.; Yuan, Changzheng (Springer, 2022)
The Chinese food system has undergone a transition of unprecedented speed, leading to complex interactions with China’s economy, health and environment. Structural changes experienced by the country over the past few decades have boosted economic development but have worsened the mismatch between food supply and demand, deteriorated the environment, driven obesity and overnutrition levels up, and increased the risk for pathogen spread. Here we propose a strategy for slimming and greening the Chinese food system towards sustainability targets. This strategy takes into account the interlinkages between agricultural production and food consumption across the food system, going beyond agriculture-focused perspectives. We call for a food-system approach with integrated analysis of potential triple benefits for the economy, health and the environment, as well as multisector collaboration in support of evidence-based policymaking.